Pierwsza próba. Krym między Ukrainą a Rosją (1989-1997) / The First Try. Crimea between Ukraine and Russia (1989-1997) - Andrzej Gil (Language, Culture, Politics)
The article deals with the problem of Russia’s aspirations to revise the geopolitical system created in Soviet times (on the example of the Crimea). It shows the activities of both local political circles and the central authorities of the Russian SFSR, and later the Russian Federation, aimed at revising the existing borders and incorporating the Crimean peninsula into Russia. The article covers the years from the collapse of the Soviet Union to the 1997 agreement between Russia and Ukraine.